2020
DOI: 10.3390/app10165691
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Image Encryption with Super-Lager-Capacity Based on Spherical Diffraction and Filtering Diffusion

Abstract: A multi-image encryption with super-large-capacity is proposed by using spherical diffraction and filtering diffusion. In the proposed method, initial images are processed sequentially by filtering diffusion and chaos scrambling. The images are combined into one image using XOR operation. The combined image is encrypted by improved equal modulus decomposition after spherical diffraction. There are three main contributions of the proposed method—(1) resisting phase-retrieval attack due to the asymmetry of spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, Wang et al proposed a multi-image asymmetric encryption method in the Fourier domain [14], which achieved multi-image encryption by combining the amplitudes and phases of different images in sequence. Moreover, multi-image encryption techniques based on fractional Merlin transform [15], ghost imaging technique [16], spherical diffraction transform [17], and optical gyrator transform [18] have been proposed respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Wang et al proposed a multi-image asymmetric encryption method in the Fourier domain [14], which achieved multi-image encryption by combining the amplitudes and phases of different images in sequence. Moreover, multi-image encryption techniques based on fractional Merlin transform [15], ghost imaging technique [16], spherical diffraction transform [17], and optical gyrator transform [18] have been proposed respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated an assuring security performance of their proposed method that could enhance the digital image security. Apart from these studies, various other methods were proposed, and interested readers are referred to References [25][26][27] and references therein for more information. Many conventional encryption techniques such as the AES algorithm are very useful.…”
Section: Introductionmentioning
confidence: 99%